Importance of correct management of bisphosphonate-related osteonecrosis of the jaw: case report and literature review - Medeiros, Cristianne Kalinne Santos; Santos, Hellen Bandeira de Pontes; Rolim, Larissa Santos Amaral; Mororó, Antonio Bruno Gomes; Germano, Adriano Rocha; Medeiros, Ana Miryam Costa de; Oliveira, Patrícia Teixeira de (Journal of Oral Diagnosis, 2018)
Introduction: Osteonecrosis results from local and systemic factors that compromise blood flow in bone tissues, being relatively frequent in maxillary bones. In recent years, there has been an increase in the incidence of new cases of medication-related osteonecrosis of the jaw (MRONJ). Objective: The aim of this study is to report a case of hard palate osteonecrosis associated with the use of bisphosphonate and to review the literature on the major clinical features, diagnosis, and management of this disorder. Case report: An 84-year-old female patient presented with a lesion to the midline of the hard palate with exposed necrotic bone. Family members reported that the patient had been on ibandronate sodium for nearly 5 years. Based on clinical and radiographic findings, the diagnosis indi-cated MRONJ. The patient underwent a surgical procedure for debridement of necrotic bone and closure of the exposed tissue by means of Z-plasty. After a 4-month follow-up, there were no clinical and radiographic signs of recurrence. Conclusion: The present case and the literature highlight the importance of proper anamnesis combined with clinical, radiographic, and laboratory findings to make an accurate diagnosis in order to provide the best therapeutic approach. In addition, the importance of dental surgeons knowledge aboutthe association between bisphosphonate therapy and osteonecrosis is very important, given the several indications of this drug and, thus, the high probability of attending to patients treated with this medication, with the aim of reducing the occurrence of new cases of MRONJ and, consequently, morbidities and their aggravation.